Analisis Kesalahan Siswa Kelas XI dalam Memecahkan Soal Cerita SPLTV Berdasarkan Kriteria Watson - Purba, Diva Novita Angely Putri; Purba, Derma Sarah Tia Wanka; Nasution, Helina Qatrunnada; Rahmah, Khalida; Syafitri, Nazwa Mutia; Siregar, Budi Halomoan (Wacana Akademika: Majalah Ilmiah Kependidikan, 2025)
This study aims to analyze the types of errors made by 11th-grade students in solving story problems involving systems of linear equations in three variables (SPLTV) using Watson’s error analysis framework. The research employed a qualitative descriptive method with 31 students from SMA Negeri 5 Medan as participants. Data were collected through written tests consisting of SPLTV story problems, teacher interviews to determine the research class, and classroom observations to support findings on students’ problem-solving processes. The data were analyzed based on Watson’s eight error categories. The findings revealed that the most frequent errors were the use of inappropriate procedures, omission of essential data, absence of final conclusions, and leaving answers blank. The main contributing factors included limited understanding of SPLTV concepts, weak algebraic skills, carelessness, and inconsistency in solving problems. These findings suggest the importance of enhancing conceptual understanding and procedural accuracy through effective learning strategies.